Grass-legume mixture and nitrogen application improve yield, quality, and water and nitrogen utilization efficiency of grazed pastures in the loess plateau - Xu, Ranran; Shi, Wei; Kamran, Muhammad; Chang, Shenghua; Jia, Qianmin; Hou, Fujiang (Frontiers in Plant Science, 2023)
We set up an experiment using three grass planting types including monoculture of alfalfa (Medicago sativa L.), monoculture of brome (Bromus inermis L.), and mixed planting of the two forages. Under each planting type, there were six management measures: grazing and no nitrogen application (GN1), grazing and 80 kg ha-1 nitrogen application (GN2), grazing and 160 kg ha-1 nitrogen application (GN3), cutting and no nitrogen application (MN1), cutting and 80 kg ha-1 nitrogen application (MN2), and cutting and 160 kg ha-1 nitrogen application (MN3). To explore the impacts of these treatments on pastures, we studied the effects on the yield, quality, and water use efficiency of three cultivated grasslands. The results showed that both alfalfa monoculture and alfalfa-brome mixed sowing grassland resulted in significantly higher fresh hay yield, crude protein yield, water use efficiency (WUE), precipitation use efficiency (PUE), nitrogen use efficiency (NUE), and agronomic efficiency of nitrogen (AEN) compared with B grassland type. In addition, the crude protein, ether extract, and crude ash content were significantly increased with alfalfa monoculture and alfalfa-brome mixed sowing while the contents of neutral detergent fiber (NDF) were reduced, thereby increasing the relative feed value (RFV) during the two years. The fresh hay yield, crude protein yield and crude protein, ether extract, crude ash content, RFV, PUE, and WUE were significantly higher in GN1, GN2, and GN3 treatments than that of MN1 treatment, while the content of NDF and acid detergent fiber (ADF) was significantly lower than MN1 treatment. Furthermore, the fresh hay yield, crude protein yield, PUE, and WUE of GN3 treatment were significantly higher than that of GN1 and GN2 treatments in both years, while the NUE and AEN were significantly higher in GN2 and GN3 treatments than that of MN3 treatment. Based on these results, mixed cropping of alfalfa and brome and application of 160 kg ha-1 nitrogen under grazing conditions is an appropriate management practice for improving the forage yield, quality, and water- and nitrogen utilization efficiency of cultivated grassland in the Loess Plateau of China.